Activity-related pain predicts pain and functional outcomes in people with knee osteoarthritis: A longitudinal study - Overton, Mark; Swain, Nicola; Falling, Carrie; Gwynne-Jones, David; Fillingim, Roger; Mani, Ramakrishnan (Frontiers in Pain Research, 2023)
Knee Osteoarthritis (OA) is a prevalent musculoskeletal condition, commonly resulting in pain and disability. However, pain and disability in this population are poorly related with the degree of structural joint damage. Underlying pain mechanisms, including activity-related pain and sensitization assessed via Quantitative Sensory Testing (QST), may better predict pain and functional outcomes of those with knee OA. Therefore, the aim of this study was to explore whether activity-related pain and sensitization assessed via QST predict future pain, function, fatigue, physical performance and quality of life outcomes in those living in the community with knee OA. Eighty-six participants with knee OA were recruited in Dunedin, New Zealand. Those eligible to participate underwent baseline testing including QST as well as measures of activity-related pain including Movement-evoked Pain (MEP) and Sensitivity to Physical Activity (SPA). Outcome measures exploring pain, function, fatigue and quality of life outcomes were collected at baseline, and two follow-up periods (two and nine weeks). Univariable linear regression models were developed followed by multivariable linear regression models for each prognostic marker adjusting for age, gender, BMI, OA duration, baseline pain intensity and socioeconomic status. Activity-related measures of pain, including MEP and SPA, demonstrated predictive associations with pain and functional outcomes prospectively in those with knee OA. Therefore, those demonstrating activity-related pain are at future risk of greater pain, disability and reduced quality of life. Larger, externally validated longitudinal studies are required which include individuals with more severe knee OA.